Strength training for teenage rugby league players - Esfahani, J. (Journal of Australian Strength and Conditioning, 2016)
Strength training for teenage rugby league players is fundamental for their physical and professional development. This form of training can offer benefits in the area of injury prevention and performance enhancement. Strength training is common practice as it produces a number of positive effects, some of the more desired outcomes are: (1) Increases in the cross-sectional area of muscle tissue due to sarcomeres being added in parallel; (2) Changes in tendon viscosity increasing stiffness of tendons; and (3) Increased fat free mass. The purpose of this paper was to outline the preseason regime, and report any strength improvements for rugby league players from 15 to 18 years of age. The players that were tested belonged to two squads; Cyril Connell Cup (under 16s) and Mal Meninga Cup (under18s). Players were tested on three exercises; (1) flat barbell bench press, (2) barbell back squat and (3) supinated pull-ups. Subsequently the squads were prescribed resistance-training programs based on these results. Programs were designed around a six to 10 rep range and delivered in the form of three different supersets. Three minutes was allocated for each superset including rest resulting in approximately 30-minute workouts. Encouraging improvements were shown across the board upon testing twice more, each six weeks apart. Cyril Connell Cup players showed average overall improvements in their bench, squat and pull-ups by 17%, 34% and 45% respectively. Mal Meninga Cup players demonstrated average improvements of 11%, 13% and 31% respectively. An added aspect of the program was that the supersets on a three-minute timer offered a degree of cardiovascular conditioning while allowing for short workout times.